2020
DOI: 10.3389/fvets.2020.00590
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and Biochemical Changes in Dogs Naturally Infected With Dirofilaria repens

Abstract: Subcutaneous dirofilariosis is a zoonotic disease emerging throughout Europe caused by the filarial nematode Dirofilaria repens . Despite its increasing prevalence, there is a large gap in knowledge of the impact of the parasite on the host. Currently classified as being non-pathogenic, recent evidence suggests that skin dirofilariosis is associated with dermatological conditions including concomitant pruritus, neoplastic processes, inflammation, and even blindness in dogs and humans. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…The goal of this article was to report the details of four cases of high D. repens microfilaremia. Hematological and biochemical findings in dogs infected with Dirofilaria repens included anemia, thrombocytopenia, leucocytosis, neutrophilia, eosinophilia, monocytosis and increased values of alkaline phosphatase, aspartate transaminase, alanine aminotransferase, blood urea nitrogen, creatinine, bilirubin as well as hypoalbuminemia, which is in keeping with results described by other authors (28,29).…”
Section: Final Conclusionsupporting
confidence: 91%
See 1 more Smart Citation
“…The goal of this article was to report the details of four cases of high D. repens microfilaremia. Hematological and biochemical findings in dogs infected with Dirofilaria repens included anemia, thrombocytopenia, leucocytosis, neutrophilia, eosinophilia, monocytosis and increased values of alkaline phosphatase, aspartate transaminase, alanine aminotransferase, blood urea nitrogen, creatinine, bilirubin as well as hypoalbuminemia, which is in keeping with results described by other authors (28,29).…”
Section: Final Conclusionsupporting
confidence: 91%
“…Helminths are known to suppress the host immune response in order to establish infection. For instance, it has been recently reported that D. repens may influence the host immune response by inducing a state of chronic in the canine host (29). It is possible that patients with high Mf counts may represent a population with pre-existing immunosuppression and are unable to naturally control or respond to the parasites.…”
Section: Final Conclusionmentioning
confidence: 99%
“…But recently, some studied suggested that subcutaneous diro lariasis is related with dermatological symptoms together with concomitant pruritus, neoplastic processes, in ammation and blindness in dogs and humans. The blood parameters in dogs were changed during infection along with deceasing of white blood cell, red blood cell and platelet and increasing of alkaline phosphatase and creatinine activity (Wysmolek et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dirofilariasis caused by D. repens is considered as a nonpathogenic disease. However, recent research has suggested that subcutaneous dirofilariasis is associated with dermatological symptoms together with concomitant pruritus, neoplastic processes, inflammation, and blindness in dogs and humans [19].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the blood parameters in dogs were altered during infection, with a reduction in the number of white blood cells, red blood cells, and platelets and an increase in alkaline phosphatase and creatinine activities [19].…”
Section: Introductionmentioning
confidence: 99%